Remediation techniques for uranium removal from polluted environment – Review on methods, mechanism and toxicology. (1st June 2022) - Akash, S.; Sivaprakash, Baskaran; Raja, V.C. Vadivel; Rajamohan, Natarajan; Muthusamy, Govarthanan
Abstract: Uranium, a radionuclide, is a predominant element utilized for speciality requirements in industrial applications, as fuels and catalyst. The radioactive properties and chemical toxicity of uranium causes a major threat to the ecosystem. The hazards associated with Uranium pollution includes the cancer in bones, liver, and lungs. The toxicological properties of Uranium are discussed in detail. Although there are many methods to eliminate those hazards, this research work is aimed to describe the application of bioremediation methods. Bioremediation methods involve elimination of the hazards of uranium, by transforming into low oxidation form using natural microbes and plants. This study deeply elucidates the methods as bioleaching, biosorption, bioreduction and phytoremediation. Bioleaching process involves bio-oxidation of tetravalent uranium when it gets in contact with acidophilic metal bacterial complex to obtain leach liquor. In biosorption, chitin/chitosan derived sorbents act as chelators and binds with uranium by electrostatic attraction. Bio reduction employs a bacterial transformation into enzymes which immobilize and reduce uranium. Phytoremediation includes phytoextraction and phytotranslocation of uranium through xylems from soil to roots and shoots of plants. The highest uranium removal and uptake reported using the different methods are listed as follows: bioleaching (100% uranium recovery), biosorption (167 g kg −1 uranium uptake), bioreduction (98.9% uranium recovery), and phytoremediation (49, 639 mg kg −1 uranium uptake). Among all the techniques mentioned above, bioleaching has been proved to be the most efficient for uranium remediation. Highlights: Bioremediation methods for removal and recovery of uranium are discussed. Toxicological properties and effects of uranium on human and other living organisms are presented. Mechanisms of uranium removal by bioremediation are elaborated. Future perspectives of uranium removal methods are presented.